Assessment of hemolytic effect of Cassia flower extracts on human RBCs - Phuse, Shital S.; Khan, Zia. H. (Journal of Drug Delivery and Therapeutics, 2018)
RBC membrane can be affected by consumption of bioactive compounds from herbs and medicinal plants. This study aimed to assess hemolytic effect of crude ethyl acetate and acetone extract from Cassia glauca flowers. Both the extracts of Cassia flowers were prepared, using Soxhlet apparatus. RBCs were washed with phosphate buffered saline and resuspended in 0.9% normal saline. These RBCs were added to different concentrations of the extracts and then incubated. After centrifugation, absorbance of the supernatant was determined by UV spectrophotometer at 540 nm. The present work shows that the fractions exhibited anti-hemolytic potential as extracts of Cassia flower showed very less percent of hemolysis when compared to standard quercetin. IC50values were found to be 23.77μg/ml for (CF EA) and 12.50μg/ml for Cassia flower in acetone(CF A)against standard which was found to be 41.75μg/ml. Extracts of Cassia flower exhibited very low hemolytic activity. Hence, it can be considered as safe to human RBCs.  In future recommend further in vitro and in vivo studies to evaluate the clinical efficacy of Cassia glauca extracts for treated several diseases.Keyword: Extract, Acetone, Ethyl acetate, Cassia glauca flowers, Hemolytic effect, RBCs